The Influence of Compensation and Motivation on Employee Performance at PT Indotama Perkasa in Bekasi District - Putra, Yustiana Effendi (Universitas Pamulang, 2024)
This research aims to determine the effect of compensation and motivation on employee performance at PT Indotama Perkasa in Bekasi Regency. The method used is explanatory research with analytical techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research are that compensation has a significant effect on employee performance by 46.1%. Hypothesis testing shows that t count > t table or (6.921 > 2.003). Motivation has a significant effect on employee performance by 36.6%, hypothesis testing obtained t count > t table or (5.647 > 2.003). Compensation and motivation simultaneously have a significant effect on employee performance with the regression equation Y = 9.751 + 0.426X1 + 0.344X2 and an influence contribution of 56.3%, the hypothesis test obtained calculated F > F table or (35.413 > 2.770).